On the improvement of the enhanced distance-based broadcasting algorithm. (1st January 2012) - Ruiz, Patricia; Bouvry, Pascal
Energy efficiency has attracted a lot of attention during the recent years, especially in mobile ad hoc networks where devices rely on batteries. Moreover, in this kind of networks the cooperation among devices forwarding packets or acting as a router is crucial for the network performance. Thus, reducing the energy consumption of each sending is a key feature that has been widely studied. In this paper we extend the study made for EDB, an enhanced distance-based broadcasting algorithm that aims at minimising the transmission power needed to broadcast a message in the network, by adding different network densities and values for the thresholds. Results showed that reducing the transmission power does not cause any detriment in the network connectivity but it can also increase the performance of the dissemination process.